When we <em>divide </em>both sides of the <em>inequality</em>,
3x > 27 by 3, <em>3x(3) > 27(3)</em>
we get x > 9, as the <em>simplified form </em>of the<em> inequality.</em>
Thus, giving us the answer of:
<em>x > 9</em>
Answer:
-65
Step-by-step explanation:
-80 - -15
Two minuses become plus
= -80+15
Subtract and keep the sign of the higher number
= -(80-15)
= -65
Answer:
When y = 1/2, the answer would be 0. When y = -4, the answer would be 9. When y = 0, the answer would be 1.
Step-by-step explanation: